PREPARATION PROCESS PT. DEBINDO ITE PARTICIPATION IN PREUNIVERSITY OF EXHIBITION EVENT INDOBUILDTECH 2017 - Dela Fatikasari, Rizki Ayu; Setiawati, Rahmi (UI Scholars Hub, 2018)
The focus of this study is discussing about pre-event exhibition preparation process of universitys in Indonesia Building Technology Expo (Indobuildtech) 2017 PT. Debindo ITE, as well as the implementation and solution for the obstacle. PT. Debindo Gave chances for 23 universities as the exhibitors for indobuildtech to show their works and abilities as a part of the architectural industry which has the same theme as the exhibitor itself.